MANAJEMEN KEPEMIMPINAN KEPALA SEKOLAH DALAM PENGUATAN BUDAYA ORGANISASI SEKOLAH: STUDI DI SD ISLAM CENDEKIA MUDA - Amelia Meilany; M. Al Aden Faqih; Liza Rifaturrahmi; Mayang Sekar; Fahrizal Muhamad Ramdan (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the principal’s leadership management in strengthening organizational culture at SD Islam Cendekia Muda, an Islamic elementary school operating across multiple units with its distinctive Allah Center Education (ACE) curriculum. This study employed a descriptive qualitative approach using a case study method. Data were collected through in-depth interviews with the principal, the vice-principal for curriculum affairs, and two homeroom teachers. The findings reveal that leadership is implemented through a layered managerial structure, delegation of authority, and the use of digital technology for hybrid supervision across school units. Organizational culture is strengthened through the integration of theocentric values in the curriculum, daily character habituation, continuous teacher development through In-House Training, and commitment-based partnerships with parents. The major challenges include limited leadership reach due to geographic distance and the diverse academic backgrounds of teachers. The study concludes that organizational culture is strengthened through the integration of data-driven management practices and Islamic spiritual values as the foundation of the school’s identity.